Analisis Pola Kegagalan Balok Sistem Rangka dengan Perkuatan di Daerah Tumpuan - Darwis, Mardis; Djamaluddin, Rudy; Irmawaty, Rita; Amir, Astiah (Center of Techonolgy (COT), Fakultas Teknik, Universitas Hasanuddin, 2020)
The previous research of using truss system reinforcement in the beam without concrete (BTR) in the tension zone causes a decrease in flexural capacity due to the failure in the area near the support. Therefore, it is necessary to add tensile reinforcement in the support zone. This study aims to analyze the ultimate capacity of the truss system concrete beam strengthened with tensile reinforcement and to analyze the effect of tensile reinforcement in support zone due to crack pattern. This study was conducted experimentally in the laboratory. The dimension of truss reinforced concrete specimens are 15 cm x 20 cm x 330 cm that added tensile reinforcement with three types of length, they are BTRP 40D, BTRP 50D, and BTRP 60D, where D (13 mm) is diameter of tensile reinforcement. The flexural test is carried out by monotonic static loading. The results showed that tensile reinforcement in BTRP 40D was not able to carry the ultimate capacity due to premature failure in the support zone. while BTRP 50D and BTRP 60D specimens can enhance the ultimate capacity without facing premature failure in the support zone. The tensile reinforcement of 60D has the highest ultimate capacity because it can carry the biggest loads and minimum crack pattern.